Facing Hymenoptera venom allergy: from natural to recombinant allergens - Perez-Riverol, Amilcar [UNESP] (2015)
Along with food and drug allergic reactions, a Hymenoptera insect Sting (Apoidea, Vespidae, Formicidae) is one of the most common causes of anaphylaxis worldwide. Diagnoses of Hymenoptera venom allergy (HVA) and specific immunotherapy (SIT) have been based on the use of crude venom extracts. However, the incidence of cross-reactivity and low levels of sensibility during diagnosis, as well as the occurrence of nonspecific sensitization and undesired side effects during SIT, encourage the search for novel allergenic materials. Recombinant allergens are an interesting approach to improve allergy diagnosis and SIT because they circumvent major problems associated with the use of crude venom. Production of recombinant allergens depends on the profound molecular characterization of the natural counterpart by combining some omics approaches with high-throughput screening techniques and the selection of an appropriate system for heterologous expression. To date, several clinically relevant allergens and novel venom toxins have been identified, cloned and characterized, enabling a better understanding of the whole allergenic and envenoming processes. Here, we review recent findings on identification, molecular characterization and recombinant expression of Hymenoptera venom allergens and on the evaluation of these heterologous proteins as valuable tools for tackling remaining pitfalls on HVA diagnosis and immunotherapy.